i^(-1) = 1/i = -i
summation from i = 1 to n i^(-1) = -ni
put if you mistyped and meant which is likely
i^(-n) it is geometic series
= -(i+i^2+i^3+..... )
= -(1-i^(n+1))/(1-i)
2006-11-22 13:49:30
·
answer #1
·
answered by Mein Hoon Na 7
·
0⤊
2⤋
If the summation is i^-1, then it would just be the same as 1/i, which is 1, no matter what n is. I don't understand: where is the n in the summation?
2006-11-22 13:47:08
·
answer #2
·
answered by Skop 2
·
0⤊
2⤋
The sum [k=1, n]â1/k is called the nth harmonic number. It is given by [0, 1]â«(1-x^n)/(1-x) dx. This can be shown by induction:
First, this formula holds where n=1, since:
[k=1, 1]â1/k = 1, and
[0, 1]â«(1-x)/(1-x) dx = [0, 1]â«1 dx = 1
Now, suppose this formula holds for some n. Then:
[k=1, n+1]â1/k
[k=1, n]â1/k + 1/(n+1)
By our inductive hypothesis:
[0, 1]â«(1-x^n)/(1-x) dx + 1/(n+1)
The last term is equal to [0, 1]â«x^n dx, so:
[0, 1]â«(1-x^n)/(1-x) dx + [0, 1]â«x^n dx
[0, 1]â«(1-x^n)/(1-x) + x^n dx
[0, 1]â«(1-x^n)/(1-x) + (x^n - x^(n+1))/(1-x) dx
[0, 1]â«(1-x^(n+1))/(1-x) dx
Thus the formula holds for n+1, and by induction, it holds for all n.
2006-11-22 15:03:08
·
answer #3
·
answered by Pascal 7
·
0⤊
0⤋
this is 1+1/2 +1/3 + 1/4 +..., right?
This is the harmonic series. To sum, let Sn be the sum to n
let S(n+1) be Sn +1/(n+1)
Hmm, I forgot!
2006-11-22 13:53:27
·
answer #4
·
answered by modulo_function 7
·
0⤊
0⤋